Retention Pool As Alternative For Flood Control Case Study Of Bapertarum Housing, Sumenep Regency - Ach. Desmantri Rahmanto; Faisal Rosihan (Litbang Pemas - Universitas Islam Lamongan, 2021)
Indonesia is a water country with thousands of rivers and hundreds of deep seas. This causes Indonesia to become a country that is very prone to flooding. But basically, there are several factors that cause this to happen, namely: natural events, drainage damage and environmental degradation caused by human activity itself. Geographically, Bapetarum Housing is an area located in a rainwater catchment area so that it is prone to flood events. High rainfall intensity can cause flood inundation as high as 30 cm. The purpose of this study is to calculate the adequacy of the retention pond to cope with flooding. The procedure for collecting research data begins with analyzing the flood, namely primary and secondary data. Meanwhile, the data analysis techniques used are planning rain analysis, rainfall intensity, flood discharge analysis, retention pond capacity. The retention pond capacity is sufficient because the dimensions of the retention pond are larger than the volume of the retention pond capacity when the flood is 6750m3>6447m3. The retention pond is planned in the downstream area of the residential river with a pool area of 50 x 40 meters and a depth of 4.5 m. The bottom condition of the pond is saturated because it is always inundated with water, the infiltration rate is constant (fc). The constant infiltration for clayey soil type is 0.5 m/day, the infiltration volume rate that occurs at the bottom of the pond is 179 m3/hour, the volume is below the threshold 8283.21 m3, infiltration time is 46 hours.